An eye tracker based on webcam and its preliminary application evaluation in Chinese reading tests. (April 2022) - Lin, Zhongjun; Liu, Yinghua; Wang, Hui; Liu, Zhengji; Cai, Sijin; Zheng, Zhicheng; Zhou, Yongjin; Zhang, Xinyu
Highlights: An eye tracking setup based on webcam are introduced and compared with a simultaneously deployed commercial eye tracker, and its preliminary application evaluation in text reading tests is introduced. Results demonstrated the application of the proposed setup can reveal the quantitative differences in reading between subjects of different age groups. It's preliminarily shown that encouraging results can be achieved with a commonly ready and easy-to-use setup can help in text reading tests. Abstract: There is increasing evidence that eye trackers can be used in neuroscience research to assess cognitive function although expensive prices or low availability still prevent its ubiquitous application. Meanwhile, in tasks such as reaction speed testing in cognitive function assessment, the requirements for spatial performance are less critical than temporal resolution. Therefore, in this report we propose an eye-tracking system based on a common web-camera, to evaluate if it's possible to achieve a decent temporal resolution for eye-tracking tasks in cognitive experiments and then further evaluate it in Chinese reading tests. The performance of the proposed setup are evaluated in comparison experiments including 62 healthy subjects, with a commercialized eye-tracker (SMI RED250) simultaneously deployed. It's found in the results that the webcam-based system showed no significant difference in the recognition accuracy of occurrence and switching of the eye movement events compared with the SMI system though the spatial eye-tracking performance is significantly worse. Then in an application experiment, cognitive-related Chinese reading tests are adapted and EMs of 27 young (18–30 years) and 28 elderly (over 60 years) readers are recorded to study their difference in Chinese reading. In the results there are significant differences in reading-time-per-sentence between young and elderly subjects. Meanwhile, a study on the reading-time-per-sentence difference using reading materials of different difficulties shows that elderly subjects are more sensitive to difficulty changes. These results preliminary demonstrated the feasibility of a Chinese reading test with a web-camera setup as an alternative option when the expensive eye-tracker is not available.